Mengembangkan Kemampuan Mengenal Bilangan dan Lambang Bilangan Pada Anak dengan Permainan Jual-Beli - Devi Wahyu Alfia Nita (incrementapedia, 2019)
This research is motivated by the school environment that develops the ability to recognize the numbers and the symbol of the number of children is still centered on the teacher, so the ability of the child is still not developed. Therefore, to develop the ability to recognize numbers and symbols of numbers need to be done in the right way, that is by using the role playing method of buying and selling. The purpose of this study to determine the ability to recognize the number and symbol of the number of children before and after the applied method of selling role play.This research uses pre-experimental design design with one-group pretest-posttest design. The subjects of this study were 18 children. Data analysis applied in this research is different test technique of pre-test and post-test (t test) from activity observation of children to know the ability to recognize numbers and symbol of number through play role of buying and selling. The result of data analysis shows the value of 21,17 and 1,74 at α 0,05 and 2,57 at α 0,01, then ˃ rejected and accepted. Thus, it can be concluded that playing the role of buying and selling affects the ability to recognize numbers and symbols of numbers in of kindergartens children.